Phytochemistry and Pharmacological Activities of Sphagneticola trilobata: A Systematic Review with Perspectives for Drug Discovery - Labhade, Sonali Dnyaneshwar; Kamadi, Suraj; Karwa, Pawan Nandkishor; Bhole, Ritesh Prakash; Kapare, Harshad Sunil; Chitlange, Sohan Satyanarayan (UI Scholars Hub, 2026)
Sphagneticola trilobata (L.) Pruski is a medicinal plant widely used in traditional medicine for its anti-inflammatory, antimicrobial, antioxidant, hepatoprotective, wound healing, and CNS depressant effects. Despite its broad pharmacolo-gical potential, clinical application is limited due to a lack of mechanistic understanding, standardization, and clinical validation. This review aims to provide a comprehensive overview of the phytochemical composition, pharmacological activities, and therapeutic potential of S. trilobata, while highlighting research gaps and suggesting future directions for clinical translation. A systematic review of scientific literature, ethnobotanical sources, and pharmacological studies was conducted, focusing on phytochemical analysis, biological activity, toxicity, and potential applications in evidence-based medicine. Phytochemical studies reveal that S. trilobata contains flavonoids, terpenoids, sesquiterpene lactones, and phe-nolic compounds. Key constituents such as kaurenoic acid, grandiflorenic acid, and wedelolactone are associated with antioxidant, anti-inflammatory, hepatoprotective, antimicrobial, antidiabetic, and anticancer properties. However, there are gaps in understanding its pharmacokinetics, mechanisms of action, and clinical relevance. Although S. trilobata shows strong pharmacological promise, further research is needed to clarify molecular mechanisms, enhance bioavailability, and conduct well-structured clinical trials. These efforts are essential to support its integration into evidence-based and modern medicinal systems.